Border politics the limits of sovereign power - Vaughan-Williams, Nick (Edinburgh University Press, 2009)
Presents a distinctive theoretical approach to the problem of borders in the study of International Relations. It turns from the current debate regarding the presence or absence of borders to consider the fundamental change that is occurring in the concept of the border in contemporary political life